Design and implementation of software tools for property verification in operational transformation - Luo, Jianlin (2014)
Operational Transformation (OT) as a real-time collaborative computing technology has been extensively studied over the past two decades. One of the aspects that has not been fully explored is the correctness of those OT systems whose operation model consists of string-wise primitive operations. To detect and resolve puzzles – subtle and characteristic collaborative editing scenarios in which an OT system may fail, in this project we devised a verification system that can independently and exhaustively cover all possible transformation cases in which puzzles may exist. This particular software tool will also be able to verify the soundness of customized string-wise transformation functions.